THE EFFECT OF COMPENSATION, LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE SATISFACTION AT PT ARARA ABADI SIAK AREA DISTRICT - Alhempi, Raden Rudi; Sitohang, Samuel; Nurmansyah, Nurmansyah; Fitrie, Souvya (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThis study aims to determine how the influence of compensation, leadership style and work environment on employee job satisfaction at PT. Arara Abadi Siak Area District. This research uses quantitative and qualitative data types and sources. The population in this study were all employees at PT. Arara Abadi Siak Area District, totaling 92 people. So the respondents are all employees at PT. Arara Abadi Siak Area District. This sampling technique was carried out using the census research method, namely research that took one population group as a whole sample and used a structured questionnaire as the main data collection tool to obtain specific information.Based on the results of this study indicate that compensation has a positive and significant effect on employee job satisfaction. Leadership style has a positive and significant effect on employee job satisfaction. The work environment has a positive and significant effect on employee job satisfaction. It can be concluded that compensation, leadership style and work environment have a positive and significant effect on employee job satisfaction at PT. Arara Abadi Siak Area District. The implication of the results of this research is that companies should pay attention to the compensation given to employees, the leadership style of the leaders, and a comfortable work environment to increase job satisfaction for employees. Keywords: Compensation, Leadership Style and Work Environment